GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2015)
A dataset containing 272 species occurrences available in GBIF matching the query: TaxonKey: Sceloporus megalepidurus Smith, 1934 Geometry: POLYGON((-102.15 15.95,-102.15 21.00,-93.78 21.00,-93.78 15.95,-102.15 15.95)) HasGeospatialIssue: false. The dataset includes 272 records from 17 constituent datasets: 1 records from Vertebrate Zoology Division - Herpetology, Yale Peabody Museum. 20 records from KUBI Herpetology Collection. 3 records from LACM Vertebrate Collection. 1 records from Computarización de las Colecciones de Anfibios y Reptiles del Centro de Investigaciones Biológicas de la Universidad Autónoma del Estado de Hidalgo. 4 records from Computarización de las colecciones de vertebrados terrestres de la Escuela Nacional de Ciencias Biológicas, IPN Fase 1: Estado de México, Hidalgo, San Luis Potosí y Tlaxcala. 2 records from Computarización de las colecciones de vertebrados terrestres de la Escuela Nacional de Ciencias Biológicas, IPN - Fases 3. 2 records from Inventario herpetofaunístico del valle semiárido de Tehuacán-Cuicatlán (continuación). 6 records from Herpetofauna de la reserva de la biósfera Valle de Tehuacán-Cuicatlán (etapa final). 26 records from Museum of Comparative Zoology, Harvard University. 103 records from Computarización de las colecciones de vertebrados terrestres de la Escuela Nacional de Ciencias Biológicas, IPN - Fases 2. 36 records from UCM Amphibian and Reptile Collection (Arctos). 2 records from Reptile Specimens. 11 records from CM Herps Collection. 1 records from NMNH occurrence DwC-A. 2 records from MVZ Herp Collection (Arctos). 50 records from Inventario herpetofaunístico del valle semiárido de Tehuacán-Cuicatlán. 2 records from CUMV Reptile Collection (Arctos).
Keywords: GBIF; biodiversity; species occurrences